Field and Laboratory-based Approach for the Determination of Friction Angle of Geological Discontinuities of Malaysian Granites - R. A Ghani; T. L Goh; A. M Hariri; Y. N Baizura (Universitas Gadjah Mada, 2011)
The basic friction angle, ?b for artificially sawn discontinuity planes for fresh granite, as determined by tilt testing, has an average value of 30º. For the natural rough discontinuity surfaces, a wide range of values have been determined for the peak friction angle, ?peak ranging from 47º to a maximum value of 80º, depending on the joint roughness coefficient (JRC). The average values of the friction angles for the different degrees of roughness were as follows: JRC 2–4 = 58°; JRC 6–8 = 60°; JRC 8–10 = 47°; JRC 12–14 = 60°; JRC 14–16 = 71° ; JRC 18–20 = 80°.